Conjoined Twins in Red Sokoto Goat - AHMAD, i.; CHAFE, U.M.; UMAR, A.A.; SALISU, M.D. (Journal of the Hellenic Veterinary Medical Society, 2020)
A case of female conjoined twins was found in Red Sokoto goat, delivered alive along with a free male kid without obstetrical assistance. The abnormal twins were examined clinically and at postmortem. Based on morphological features, they could be classified as thoraco-omphalopagus symmetrical conjoined twins. Autopsy showed that fusion occurred at ventral-midline from the cranial region of the thorax to abdomen caudal to the umbilicus; thus, only head, neck and pelvis were separated. Genetic factors could be suspected in this case. This is the first report of thoraco-omphalopagus symmetrical twinned goat in Nigeria.